Digital pedagogy, academic freedom and responsibility in the post-COVID-19 pre-service teacher education - Chigona, A. (South African Journal of Higher Education, 2025)
When coronavirus hit in 2020, learning institutions could not have imagined that curriculum delivery would be disrupted to the point that face-to-face teaching and learning could impossible due to a lockdown. Digital technology was deployed for remote teaching and learning. The lockdown accelerated digital transformation in learning institutions. The transformation required a new pedagogy for learning to be effective. Hence, educators in teacher education programs cannot continue to teach the pre-service teachers the same way they used to if the prospective teachers are to be adequately equipped to teach in this digital era. This means that the digital transformation in the post-COVID-19 affected teacher educators’ responsibilities and freedoms for equipping student teachers. Hence this article analyses teacher educators’ lived experiences of their academic freedoms and responsibilities in the post-COVID-19 when equipping student teachers to teach with and through new technologies. Results of the study show that digital technologies can promote academic freedom by enhancing access, engagement, efficiency, and free exchange of ideas. Digital tools can also provide affordable access to international collaboration. Teacher educators around the globe are collaborative and exchange ideas virtually. Educators can invite guest lecturers from far to their online classes. The collaborations are proving to be more cost effective than when people had to travel to meet in person. However, those lacking digital skills, as well as those lacking digital resources and technical support, are missing out on the potentials the digital technology could enhance in their work.